Green synthesis of CaO nanoparticles from chicken eggshells: antibacterial, antifungal, and heavy metal (Pb2⁺, Cr2⁺, Cd2⁺ and Hg2⁺) adsorption properties - Hemmami, Hadia; Zeghoud, Soumeia; Ben Amor, Ilham; Alnazza Alhamad, Ali; Tliba, Ali; Alsalme, Ali; Cornu, David; Bechelany, Mikhael; Barhoum, Ahmed (Frontiers in Environmental Science, 2024)
Background: Chicken eggshells, a common poultry byproduct, are rich in calcium and provide a sustainable source for producing calcium oxide nanoparticles (CaO NPs). Their use in ecofriendly synthesis aligns with the growing emphasis on sustainable materials for environmental and biomedical applications.Objectives: This study develops an eco-friendly method for synthesizing CaO NPs from chicken eggshells, characterizes their physicochemical properties, and evaluates their antibacterial and antifungal activities. It also tests their effectiveness in removing heavy metal ions (Pb²⁺, Cr²⁺, Cd²⁺, and Hg²⁺) from aqueous solutions.Methods: CaO NPs were synthesized by calcining chicken eggshells at 700°C for 7 hours.Comprehensive characterization included analysis of crystalline structure, morphology, optical properties, bandgap energy, chemical composition, and thermal stability. Antibacterial and antifungal activities were tested using the well-agar diffusion method. Batch adsorption experiments evaluated heavy metal ion removal under varying conditions of pH, temperature, stirring time, and adsorbent concentration.Results: The synthesis produced spherical, single-crystal CaO NPs with diameters ranging from 5 to 30 nm and a crystalline size of approximately 20 nm. The nanoparticles had a bandgap energy of about 4.7 eV. Significant antibacterial activity was observed against Staphylococcus aureus, Klebsiella pneumoniae, and Escherichia coli, with increasing inhibition zones correlating with nanoparticle concentration. The CaO NPs also effectively inhibited Candida albicans. For efficient metal ion removal, the optimal conditions were found to be 30 minutes at pH 6 with 40 mg of CaO NPs at 25°C, achieving recovery rates of 98% for Pb²⁺, 97% for Cd²⁺, 97% for Cr²⁺, and 97% for Hg²⁺. For near-complete removal, extending the process to 70 minutes at pH 6 with 40 mg of CaO NPs at 45°C achieved the highest recovery rates: 99% for Pb²⁺, 98% for Cd²⁺, 99% for Cr²⁺, and 99% for Hg²⁺, though this approach involves higher energy and cost.Conclusion: CaO NPs derived from chicken eggshells are effective antibacterial agents and adsorbents for heavy metal removal. These findings highlight their potential for sustainable applications in environmental and biomedical fields.